APPLICATION OF A PROBLEM-BASED LEARNING MODEL TO IMPROVE STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITY ON THE SUBJECT OF ONE-VARIABLE LINEAR EQUATIONS AND INEQUALITIES IN CLASS VII OF SMP NEGERI 1 SIMANINDO FY 2021/2022 - Anni Hartini Marito Sitanggang (Sean Institute, 2023)
The application of a problem-based learning model to improve the mathematical skills of class VII-A students of SMP Negeri 1 Simanindo is a class action (PTK). The research subject was for 16 batch 1 people where the object of research was the ability to think creatively in mathematics of students in linear equations and inequalities for one variable TA 2021/2022. Class action (PTK) consists of 2 cycles, each 2 meetings. Before giving the action, they are first given an initial test and at the end of each cycle are given a test of mathematical creative thinking ability. The results of the analysis of the initial test data showed that the number of students who achieved learning mastery from the initial test was 2 out of 16 students or 12.5% ​​with a class average of 42.66. The results of data analysis in cycle I after applying the problem-based learning model showed that the number of students who achieved mastery learning was 10 out of 16 students or 62.5% with a class average of 63. The results of data analysis at the end of cycle II with the same learning obtained the number of students achieving learning completeness is 14 out of 16 students or 87.5% with an average of 77. This means that there is an increase in students' creative thinking skills from cycle I to cycle II. Based on the classical mathematics completeness criteria, this learning has achieved the classical completeness target. This means that there is an increase in students' creative thinking skills from cycle I to cycle II. Based on the classical mathematics completeness criteria, this learning has achieved the classical completeness target. This means that there is an increase in students' creative thinking skills from cycle I to cycle II. Based on the classical mathematics completeness criteria, this learning has achieved the classical completeness target.